Methylphenidate and Flexible Thinking in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The acute effects of methylphenidate (MPH) in 3 dosages (0.3, 0.6, and 0.9 mg/kg) on the performance of 17 ADHD children in tests of cognitive flexibility were evaluated at the Departments of Psychology and Pediatrics, McGill University-Montreal Children's Hospital Research Institute, Canada.